2, 2′-Dipyridylamino-based ligands with substituted alkyl chain groups and their mononuclear-M(ii) spin crossover complexes1. Issue 30 (14th August 2015) - Scott, Hayley S.; Moubaraki, Boujemaa; Paradis, Nicolas; Chastanet, Guillaume; Létard, Jean-François; Batten, Stuart R.; Murray, Keith S.
<x xml:space="preserve">Abstract</x> Fundamental structural, magnetic and photomagnetic properties of Fe(ii) and Co(ii) complexes of alkyl-chain substituted ligands are described.